Longitudinal maternal hemodynamics in pregnancies affected by fetal growth restriction. (3rd May 2017) - Stott, D.; Papastefanou, I.; Paraschiv, D.; Clark, K.; Kametas, N. A.
ABSTRACT: Objective: Fetal growth restriction (FGR) is a powerful determinant of poor perinatal outcome. From our previous work in pregnancies at high risk of development of hypertension we found impaired cardiovascular adaptation early in gestation in those destined to deliver growth‐restricted infants. In this study, we monitored serially maternal hemodynamics from the first to third trimester in a similar high‐risk cohort, in order to determine whether this distinct hemodynamic profile found at presentation persisted throughout pregnancy in those complicated by FGR. Methods: This was a prospective observational study based at a specialist antenatal hypertension clinic at a tertiary hospital in London. Maternal hemodynamics were evaluated serially using a non‐invasive bioreactance method in pregnant women referred to the clinic with a history of chronic hypertension or a history of hypertensive disorder in a previous pregnancy. Differences in maternal hemodynamic parameters were compared between women who delivered a baby with a birth weight ≥ 10 th vs < 10 th percentile and ≥ 5 th vs < 5 th percentile. Results: Eighty‐four pregnant women were included in the study. Mean gestational age at presentation was 14.3 weeks. Sixteen women delivered babies with a birth weight < 10 th percentile and 11 with a birth weight < 5 th percentile. In pregnancies with a birth weight ≥ 10 th percentile, longitudinal maternal hemodynamics showed a pattern consistent with well‐established physiological changes in pregnancy, i.e. a reduction in vascular resistance and an increase in cardiac output with advancing gestation until mid‐pregnancy. However, women who delivered babies with a birth weight < 10 th percentile showed a static pattern with no change during gestation and lower cardiac output and higher peripheral vascular resistance. Similar differences were seen when the 5 th percentile was used to discriminate between appropriately‐grown and growth‐restricted babies. Conclusion: Serial assessment of maternal hemodynamics in high‐risk women identifies distinctive trends associated with pregnancies destined to deliver babies with birth weights < 10 th and < 5 th percentiles. These pregnancies have a suppressed and static maternal cardiac output and stroke volume, and have consistently raised peripheral vascular resistance. This suggests that, in women with chronic hypertension or a history of hypertensive disorder in a previous pregnancy, FGR is associated with a primary and persistent failure of maternal cardiovascular adaptation in pregnancy. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.